Increased Visual Attentional Demands Alter Lower Extremity Sidestep Cutting Kinematics in Male Basketball Players - Koen T.H. Rikken; Tom Panneman; Fabian Vercauteren; Alli Gokeler; Anne Benjaminse (North American Sports Medicine Institute, 2024)
# Background In basketball, changing direction is one of the primary mechanisms of anterior cruciate ligament (ACL) injury, often occurring within complex game situations with high cognitive demands. It is unknown how visual attention affects sidestep cutting kinematics during the entire energy absorption phase of the cut in an ecologically valid environment. # Purpose The purpose of this research was to study the effect of added cognitive load, in the form of increased visual attentional demands, on sidestep cutting kinematics during the energy absorption phase of the cut in an ecologically valid environment. # Study Design Crossover Study # Methods Fifteen male basketball players (aged 22.1 ± 2.3) performed ten sidestep cutting movements without (BASE) and with (VIS) a visual attention dual task. 3D kinematics of the hip, knee and ankle were recorded utilizing Xsens IMU motion capture. Temporal kinematics were analyzed using Statistical Parametric Mapping. Discrete time point kinematics were additionally analyzed at initial contact (IC) and at peak knee flexion utilizing paired t-tests. Effect sizes were calculated. # Results Hip flexion was significantly reduced in the VIS condition compared to the BASE condition (p<0.01), including at IC (VIS 35.0° ± 7.2°, BASE 40.7° ± 4.9°, p=0.02, d=0.92) and peak (VIS 37.8° ± 9.7°, BASE 45.5° ± 6.9°, p=0.001, d=0.90). Knee flexion was significantly reduced in the VIS condition, in comparison to the BASE condition (p<0.01), at peak (VIS 59.9° ± 7.5°, BASE 64.1° ± 7.4°, p=0.001, d=0.55). # Conclusion The addition of visual attention during sidestep cutting altered lower limb kinematics, which may increase ACL injury risk. It is suggested that ACL injury risk screening and prevention should include sidestep cutting with visual attentional demands, in order to mimic the cognitive demands of the sports environment. # Level of Evidence 3